Anticorrosive performance of MoO4-2-doped polyaniline conductive polymer - BRINIS, Naima (Biopolymer Applications Journal, 2024)
Electrodeposition polyaniline (PANI) and polyaniline doped (PANI-MoO -2) coatings on steel was prepared in oxalic acid solution by potentiodynamic polarization technique. Morphology of the surface coatings was analyzed by scanning electron microscopy (SEM). The protective properties and electrochemical behavior of such coatings in 0.5MH2SO4 pH0.3 solution were investigated using open-circuit potential versus time of exposure and electrochemical impedance spectroscopy (EIS). It was shown that PANI coating presented an anodic protection and their doping by molybdate ions increased considerably the protection time.